Culinary MSME Survival Strategy in Maintaining Their Existence During The Covid-19 Pandemic - Ar Ridha, Gt Syifa Noor; El Wafa, Faqih (JES (Jurnal Ekonomi Syariah), 2024)
This research is motivated by the covid-19 virus, which requires people to stay at home; of course, this impacts all industries, especially MSMEs in the culinary sector. The covid-19 pandemic has forced culinary businesses to adjust their strategies to continue to survive. The research aims to determine the impact of covid-19 on Culinary MSMEs and the use of customer relationship management (CRM)as a way for MSMEs to survive during the covid-19 pandemic. This type of research is field research with a qualitative descriptive approach. The data used was obtained from interviews with 10 MSME actors. The results of the study show that during the pandemic, culinary MSME actors in Barabai District experienced the impact of a lack of buyers, decreased income turnover, increased production of the main ingredients, experienced distribution obstacles, and decreased sales, so to survive, culinary MSME actors in Barabai District adopted a survival strategy by increasing improvements. Product and service quality, utilization of technology with digitalization schemes, and maximizing customer relationship marketing (CRM) loyalty.